HAKIKAT PENDIDIK DALAM PENDIDIKAN ISLAM - Dhea Nur Halimah; Mukhlisin; Mohammad Thoriq Aqil Fauzi (Dar El-Falah, 2023)
An educator is someone who has an obligation or profession to teach, educate,guide, provide experience to students with their knowledge which aims to geta good and right education. The rest in Islamic education educators have theresponsibility to direct their students to the guidance of Islamic teachings andmake them as pious beings. Educators also have a very big task, includingforming and building the personality of students to become someone who isuseful for religion, homeland, and nation. The teacher's duty is to preparehuman beings who are expected to be able to build the personality of studentsto become good and useful people with predetermined procedures. The criteriafor becoming a professional educator can go through several stages includinghaving the talent and ability to be a teacher, having extensive knowledge and experience, having the ability to organize and manage classes and also goodat socializing and so on.